2013
DOI: 10.1021/am401418b
|View full text |Cite
|
Sign up to set email alerts
|

Surface Passivation Effect on the Photoluminescence of ZnO Nanorods

Abstract: We report an investigation of the impact of surface passivation on the optical properties of ZnO nanorods. Al2O3 coating and hydrogen plasma treatment were used to passivate the surface states. It was found that Al2O3 coating led to the suppression of the deep level emissions, while hydrogen plasma treatment completely quenched the deep level emissions. It was confirmed that the surface states of the as-grown ZnO nanorod arrays indeed contributed to the deep level emissions. Evidence was also provided that sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
63
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(67 citation statements)
references
References 28 publications
4
63
0
Order By: Relevance
“…Chen and co-workers reported the effect of surface modification by self-assembled monolayer on the ZnO film ultraviolet sensor, 60 and examined the surface passivation effect on the photoluminescence of ZnO nanorods. 61 The results confirmed that the surface treatment of ZnO nano/microstructures is an effective and simple approach to improve some important properties of nanocomposites. Concerning the photocatalysts or dye sensitive solar cells, etc., the key issues are the generation, separation, and transfer of charges generated by visible light.…”
Section: Introductionsupporting
confidence: 62%
“…Chen and co-workers reported the effect of surface modification by self-assembled monolayer on the ZnO film ultraviolet sensor, 60 and examined the surface passivation effect on the photoluminescence of ZnO nanorods. 61 The results confirmed that the surface treatment of ZnO nano/microstructures is an effective and simple approach to improve some important properties of nanocomposites. Concerning the photocatalysts or dye sensitive solar cells, etc., the key issues are the generation, separation, and transfer of charges generated by visible light.…”
Section: Introductionsupporting
confidence: 62%
“…Moreover, additional radiative recombination emission can be caused by F doping (and possibly by H doping, as explained below) in the near surface region, which would contribute to the enhanced NBE. 67 Thus, by SF 6 plasma treatment both surface passivation effect and probably doping of the near surface region may be responsible for the observed changes in the PL spectra.…”
Section: Introductionmentioning
confidence: 96%
“…1 It possesses many important applications in electronic and optical devices. 2,3 Therefore, the controlled synthesis of various one-dimension (1D) ZnO nanostructures, such as ZnO nanorods (NRs), 4 ZnO nanowires (NWs), 5 and ZnO nanocables, 6 has attracted considerable interest due to their novel properties. Zhang et al reported that ordered ZnO NRs-based heterojunction shows improved electroluminescence (EL) performance and can be used in light-emitting diodes.…”
Section: Introductionmentioning
confidence: 99%